(NmIHAIL bULGAKOW (B;s (NpISATELX I L@BOWX (B/s - (NsTRONGIN(B, (NwARLEN lXWOWI^(B.s ((NmOSKWA (B:s (Nast(B-(NpRESS(B,s (Nast(B-(NpRESS KN(B.,s, 2004)
(NiMQ m(B. (NbULGAKOWA [IROKO IZWESTNO ^ITATEL@ PO ROMANAM (B"(NmASTER I mARGARITA(B" (NI (B"(NbELAQ GWARDIQ(B", (NPOWESTQM (B"(NsOBA^XE SERDCE(B" (NI (B"(NrOKOWYE QJCA(B". (Nw TRUDNYE MINUTY VIZNI EGO PODDERVIWALI VEN]INY(B, (NKOTORYH ON L@BIL I KOTORYE L@BILI EGO(B.s
Keywords: (NbULGAKOW(B, (NmIHAIL aFANASXEWI^s -- 1891-1940; (NrUSSKAQ LITERATURA (B- (NS (B1917 (NG(B.- (NbIOGRAFIQ PISATELQs; (Nl@BOWX W VIZNI m(B.(Na(B. (NbULGAKOWAs